Duty of candour and the disclosure of adverse events to patients and families. (January 2014) - Birks, Yvonne
The disclosure of adverse events to patients or their families who have been affected is considered to be a central feature of high quality and safer patient care, but despite this, as few as 30% of harmful errors may currently be disclosed to patients. Advocates of open disclosure propose that failing to communicate effectively with patients following adverse events may have negative repercussions for all stakeholders. The disclosure of adverse events and errors to patients and their families is partly fulfilling the duty of candour advocated in the numerous recent reports into the quality and safety within the NHS. This paper considers why disclosure remains challenging for organisations and professionals alike, despite guidance and in a clear moral imperative and commitment from stakeholders to transparency in healthcare.